Enhanced bioelectroremediation of heavy metal contaminated groundwater through advancing a self-standing cathode - Ali, Jafar; Zheng, Changhong; Lyu, Tao; Oladoja, Nurudeen Abiola; Lu, Ying; An, Wengang; Yang, Yuesuo (Elsevier, 2024)
Hexavalent chromium (Cr(VI)) contamination in groundwater poses a substantial global challenge due to its high toxicity and extensive industrial applications. While the bioelectroremediation of Cr(VI) has attracted huge attention for its eco-friendly attributes, its practical application remains constrained by the hydrogeochemical conditions of groundwater (mainly pH), low electron transfer efficiency, limitations in electrocatalyst synthesis and electrode fabrication. In this study, we developed and investigated the use of N, S co-doped carbon nanofibers (CNFs) integrated on a graphite felt (GF) as a self-standing cathode (NS/CNF-GF) for the comprehensive reduction of Cr(VI) from real contaminated groundwater. The binder free cathode, prepared through electro-polymerization, was employed in a dual-chamber microbial fuel cell (MFC) for the treatment of Cr (VI)-laden real groundwater (40 mg/L) with a pH of 7.4. The electrochemical characterization of the prepared cathode revealed a distinct electroactive surface area, more wettability, facilitating enhanced adsorption and rapid electron transfer, resulting in a commendable Cr(VI) reduction rate of 0.83 mg/L/h. The MFC equipped with NS/CNF-GF demonstrated the lowest charge transfer resistance (Rct) and generated the highest power density (155 ± 0.3 mW/m2) compared to control systems. The favorable electrokinetics for modified cathode led to swift substrate consumption in the anode, releasing more electrons and protons, thereby accelerating Cr(VI) reduction to achieve the highest cathodic coulombic efficiency (C.Eca) of80 ± 1.3 %. A similar temporal trend observed between Cr(VI) removal efficiency, COD removal efficiency, and C.Eca, underscores the effective performance of the modified electrode. The reusability of the binder free cathode, exemption from catholyte preparation and the absence of pH regulation requirements highlighted the potential scalability and applicability of our findings on a larger scale.
Keywords: Bioelectricity; Carbon nanofibers; Chromium; Electroremediation; Green technologies; Toxic metals